Socio-political and Religious Contributions of Sir Syed Ahmad Khan - Dr. Naseem Akhter; Dr. Salman Arif; Dr. Sohail Akhtar (الآفاق اسلامی و تحقیقی مجلہ, 2024)
Sir Syed Ahmad Khan is considered well known intellectual of India and he served as most remarkable educational reformer during Colonial era. Sir Syed considered an important Muslim leader in India who had good collaboration with English Statesmen after 1857. With socio-political contribution, Syed Ahmad Khan, who had profound a political insight presented his religious ideas. Although his religious concepts created different conspiracies among the Muslims of India, especially the religious class opposed his religious theories and declared these stance against the spirit of Islam. This paper is an analytical study about the religious thoughts of Sir Syed which critically explore the religious thoughts of Sir Syed Ahmad Khan.